Stand und Perspektiven der deutsch-japanischen Wirtschaftsbeziehungen - Spinner, Werner (Zeitschrift für Japanisches Recht, 2003)
This lecture discusses the current economic relations between Germany and Japan. The author heads the Japan Initiative of the Asia-Pacific Committee of the German Economy. Basically, there are no frictions at all between the two countries, but this happy state of being must not lead to idleness. There seems to be a growing shift in the focus of German industry toward the People’s Republic of China with its perceived huge market potential. However, it should not be overlooked that Japan is still by far the most important economy in Asia, with an annual per capita income 40 times as high as China’s. Further, there is an enormous potential for technological innovation in Japan. Thus, although entry into such a highly developed market might be difficult, it is worth the effort. Many German companies are highly successful in Japan. Besides, being there and therefore being close to German industry’s most intense competitor in many fields is a significant advantage in itself, because being present in the Japanese market forces the companies to be extremely efficient. This in turn gives them a cutting edge for competing in the world market. The “German Year” in 2005–2006 provides a good chance for presenting the country and its companies in Japan. (The Editors)